PENGGUNAAN MEDIA MODEL DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PERUBAHAN LINGKUNGAN FISIK TERHADAP DARATAN DI KELAS IV SD NEGERI NO. 03 KAMPUNG TENGAH KECAMATAN BAYANG - Murna Yenti (Inovasi Pendidikan, 2017)
From the implementation of the research on media usage models in improving student learning outcomes in learning changes the physical environment on the mainland do give the conclusion that the study carried out in accordance with the implementation plan has been prepared. During the learning process assessment using signs characteristic of the application of learning media usage model in learning physical changes to the land kingkungan both from the aspect of teachers and students. In addition, the assessor also carried out on the group's activities of individuals and groups. To score the final test score was obtained by summing the scores obtained in the learning process divided by the total number of students. If the final score is obtained by the students, ranging from 75% -100%, the student is otherwise completed in learning. If the final score is obtained by students <75%, the student in question has not been declared complete in learning. To declare success or failure of the action taken be seen from the percentage of the total student mastery. This percentage is obtained by the number of students who achieve mastery divided by the number of students overall, and then multiplied by 100%. If the percentages obtained ranged between 75% -100% means the act declared complete, if the percentage obtained <75% -100% means the actions taken unresolved and must be repeated in the next cycle. Key words: media model, student learning outcomes, changes physical environment, mainland